2021
DOI: 10.1051/metal/2020083
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of high-strength biochar composite briquette for blast furnace ironmaking

Abstract: In this research, using iron-oxide fines (average size: 2.5 μm) and biochar fines (average size: 50.0 μm), the biochar composite briquette (BCB) for blast furnace (BF) application was prepared by cold briquetting followed by heat treatment. The preparing conditions were optimized regarding its cold crushing strength. Anti-pulverization capability, reaction development, and structure evolution of the optimally-designed BCB under simulated BF conditions were then examined. Results of optimizing BCB preparation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The difficulty in using BCB in BF is its poor strength under the BF environment. 17) The authors of current study 18) proposed to prepare BCB using cold briquette followed by heat treatment. Under the simulated BF conditions, the cold crushing strength of BCB after partial reaction was from 1 500 N/briquette to 5 500 N/briquette, indicating the BCB is permittable for application as a BF burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in using BCB in BF is its poor strength under the BF environment. 17) The authors of current study 18) proposed to prepare BCB using cold briquette followed by heat treatment. Under the simulated BF conditions, the cold crushing strength of BCB after partial reaction was from 1 500 N/briquette to 5 500 N/briquette, indicating the BCB is permittable for application as a BF burden.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that, Under the BF conditions, the BCB underwent five stages of reduction by BF gas, partial self-reduction and reduction by BF gas, full self-reduction, partial self-reduction and gasification by BF gas, and gasification by BF gas. 18,19) To evaluate the coke saving level by BCB charging and to optimize the conditions of BF operation, it is important to understand BCB reaction in actual BF and its influence on the BF in-furnace state. Owing to the high-pressure, high-temperature, and hazardous environment in BF, it is impossible to measure directly the required information in BF.…”
Section: Introductionmentioning
confidence: 99%